LITERASI PEDOMAN DALAM PENDIDIKAN ISLAM - Febi Aisqil Jamilah; Siti Dela Yanti; Suci Rahmadani Simanjuntak (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This paper explores the importance of literacy in Islamic education as a foundation for character building, spirituality, and critical thinking skills. Literacy in Islam is not limited to the ability to read and write, but also includes a deep understanding of divine revelation, moral values, and life ethics. This study uses a qualitative approach through library research by examining Qur’anic verses such as Surah Al-‘Alaq (verses 1–5) and Surah Ali Imran (verses 190–191), along with scholarly interpretations. The findings indicate that Islamic literacy education should cover three main dimensions: literacy towards sacred texts, critical thinking guided by the principle of tabayyun (verification), and moral and spiritual awareness. Therefore, strengthening literacy based on Islamic values is essential in shaping a generation that is not